Effect of short‐term endurance training on venous compliance in the calf and forearm differs between continuous and interval exercise in humans - Anna Oue; Michiko Saito; Yasuhiro Iimura (Physiological Reports, 2019)
Abstract We examined whether the effect of short‐term endurance exercise training on venous compliance in the calf and forearm differed between continuous and interval workloads. Young healthy volunteers (10 women and 16 men) were randomly assigned to continuous (C‐TRA; n = 8) and interval (I‐TRA; n = 9) exercise training groups, and a control group (n = 9). Subjects in the C‐TRA group performed a continuous cycling exercise at 60% of heart rate reserve (HRR), and subjects in the I‐TRA group performed a cycling exercise consisting of alternating 2‐min intervals at 40% HRR and 80% HRR. Training programs were performed for 40 min/day, 3 days/week for 8 weeks. Before and after training, limb volume in the calf and forearm was measured with subjects in the supine position by venous occlusion plethysmography using a venous collecting cuff placed around the thigh and upper arm. Cuff pressure was held at 60 mmHg for 8 min and then decreased to 0 mmHg at a rate of 1 mmHg/s. Venous compliance was calculated as the numerical derivative of the cuff pressure–limb volume curve. Calf venous compliance was increased after I‐TRA, but not C‐TRA. Forearm venous compliance was unchanged after C‐TRA or I‐TRA. These results suggest that the adaptation of venous compliance in response to endurance training for 8 week may occur in interval but not continuous exercise bouts and may be specific to the exercising limb.